Implementation of the Mosque Management Information System (SIMAS) in Improving Services at the Ministry of Religious Affairs Office Kendal Regency - Dika, Muhammad; Hakim, Lukmanul; Susanto, Dedy (Munazzama: Journal of Islamic Management and Pilgrimage, 2023)
The SIMAS (Mosque Management Information System) application from the Indonesian Ministry of Religious Affairs is used to manage data on mosques and musallas online throughout Indonesia. This research used a descriptive qualitative method with data collection techniques in the form of interviews, observation, and documentation. The results of data analysis showed a significant increase in services at the Ministry of Religious Affairs Office due to the use of SIMAS. The previous manual data collection on mosques and musallas (musallas) has been replaced with an online method via the SIMAS website with collaboration between various agencies, including the Office of Religious Affairs and sub-districts. It has accelerated and improved effectiveness of services in the office. With adequate human resources, SIMAS has become an efficient tool for inputting data on mosques and musallas. This research highlights the important role of SIMAS in improving efficiency and service at the Kendal Regency Ministry of Religious Affairs Office.